Analyzing the Circular Economy of the EU Countries: Evidence on Environmental and Sustainable Development Perspectives - Gokgöz, Fazil; Yalçin, Engin (Emerald Publishing, 2025)
There is now a significant disparity between production and consumption because the world's population is growing exponentially and nonrenewable resources are running out. Large volumes of waste have been produced in addition to the enormous use of natural resources. A dynamic idea that can be monitored at the country level, the circular economy (CE), which resulted from the fusion of sustainable development, has a major impact on human progress in solving aforementioned problems. The CE concept has surfaced as a viable and successful way to start the shift to sustainable development. The increasing focus on sustainable development goals compels nations to adopt efficient performance management strategies. Monitoring the country's progress in the CE would yield valuable information that might help with the successful development of sustainability improvement initiatives. Thus, we aim to assess the CE efficiency of the EU countries by using the bootstrap data envelopment analysis (DEA) technique, which overcomes the limitations of the traditional DEA technique, such as point estimation and the inability to obtain statistical inference. The results reveal variations in efficiency across countries and years, with bias-corrected scores presenting a more accurate reflection of performance trends. © 2025 Fazil Gokgoz and Engin Yalçin. All rights reserved.
Keywords: Bootstrap data envelopment analysis; Circular economy; Efficiency; European Union; Sustainability